EXPRESS-EVALUATION OF THE EFFICIENCY OF IMPLEMENTATION OF ENERGY SAVING ACTIVITIES - Litvin V.I. (Problems of the Regional Energetics, 2012)
Pre-analyze algorithm of estimation the energy conservation measures results is described in the article. It based on the Kohonen neural networks and allows making conclusions about the savings and needed costs using the statistic data about the similar projects